2022
DOI: 10.1002/slct.202104148
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina Biomass‐Loaded Thermoplastic Polyurethane/Polycaprolacton (TPU/PCL) Nanofibrous Mats: Fabrication, Characterization, and Antibacterial Activity as Potential Wound Healing

Abstract: The development of antibacterial products with therapeutic properties has become a popular human health trend. Herein, for the first time, we described an effective antibacterial thermoplastic polyurethane/polycaprolacton (TPU/PCL) composite nanofibers loaded with the spirulina biomass by electrospinning method for wound care applications. The chemical, microstructural, mechanical, wettability properties and antibacterial activities of produced electrospun TPU/PCL/spirulina fibers with varied spirulina concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…A polymeric biomaterial is aimed to interact with biological systems in evaluating, repairing, restoring, or replacing any tissue, organ, or function of the body [ 8 ]. Polymers have great potential because of their chemical flexibility and a wide variety of physical and mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…A polymeric biomaterial is aimed to interact with biological systems in evaluating, repairing, restoring, or replacing any tissue, organ, or function of the body [ 8 ]. Polymers have great potential because of their chemical flexibility and a wide variety of physical and mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced water uptake tends to absorb the wound exudate, which helps keep the wound region dry and prevent possible infections . As shown in Table S1, the water uptake ratio of the drug-loaded nanofibers increased over time compared to PUF, which was hardly changed even after 72 h. The poor water uptake behavior of PUF is attributed to its hydrophobic nature . The more hydrophilic drugs and AuNRs are beneficial to enhance the hydrophilicity and water infiltration through a water insoluble barrier .…”
Section: Resultsmentioning
confidence: 99%
“…22 As shown in Table S1, the water uptake ratio of the drug-loaded nanofibers increased over time compared to PUF, which was hardly changed even after 72 h. The poor water uptake behavior of PUF is attributed to its hydrophobic nature. 23 The more hydrophilic drugs and AuNRs are beneficial to enhance the hydrophilicity and water infiltration through a water insoluble barrier. 24 The nanofibers are a matrix-based system, in which the drug is uniformly distributed and the infiltration of water leads to the swelling of the polymer matrix to some extent too.…”
Section: Preparation and Characterization Of Drug-loaded Nanofibersmentioning
confidence: 99%
“…In other study, thermoplastic polyurethane/ polycaprolactone (TPU/PCL) nanofibers were fabricated via electrospinning. [21] The study showed all nanofibers can be a potential wound dressing material.…”
Section: Introductionmentioning
confidence: 94%
“…In their study, usinic acid – loaded pectin and sodium alginate (SA) biomaterials were casted into the polyester fiber. In other study, thermoplastic polyurethane/polycaprolactone (TPU/PCL) nanofibers were fabricated via electrospinning [21] . The study showed all nanofibers can be a potential wound dressing material.…”
Section: Introductionmentioning
confidence: 99%